2007
DOI: 10.1002/app.27091
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the viscoelastic and mechanical properties of tightly cross‐linked polythiourethane networks

Abstract: Both viscoelastic behavior and plastic deformation in compression were investigated on new polythiourethane networks based on diisocyanates and tri-or tetra-thiols. Dynamic mechanical analysis was used to characterize the mechanically-active a and b relaxations as a function of crosslink density and nature of the diisocyanate. Data molecular analysis on these novel materials led to conclusions in good agreement with earlier statements on the well-known epoxy-amine networks. Besides, consideration of the relaxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 17 publications
(18 reference statements)
0
24
0
Order By: Relevance
“…The motional processes responsible for this secondary transition were further investigated. As shown in another publication [27] and resulting from the consideration of a series of polythiourethane networks in which the type of isocyanate and thiol have been modified in order to vary the crosslink density, the β motions present a cooperative character on a rather short scale, by propagating through the thiol structure.…”
Section: Dynamic Mechanical Analysismentioning
confidence: 98%
“…The motional processes responsible for this secondary transition were further investigated. As shown in another publication [27] and resulting from the consideration of a series of polythiourethane networks in which the type of isocyanate and thiol have been modified in order to vary the crosslink density, the β motions present a cooperative character on a rather short scale, by propagating through the thiol structure.…”
Section: Dynamic Mechanical Analysismentioning
confidence: 98%
“…As in the case of amides and carbamates [, ], bis(thiocarbamates) are characterized by the presence of N–CO bond having a partially double bond character, which results in the presence of the two s‐cis and s‐trans conformations. In our case and as can be seen from Table , the benzyl and phenyl derivatives show the coexistence of the two conformers (i.e., two NH NMR signals), while only one signal was observed in the 1 H NMR spectra for the other derivatives at room temperature (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These may consist in a controlled variation of the resin and hardener type, of their stoichiometric amount, or in a change of the resin processing, i.e., the curing cycle parameters. Various works investigated how the mechanical behavior of epoxy resins is affected by: the stoichiometric ratio [2–5], the type of resin and hardener [3, 6–8], the employ of chains extenders [9], and the employ of blends of different diepoxy monomers [10]. It was revealed that even relatively small changes in the material composition, as for example a variation in hardener and resin relative amounts, can promote changes in the mechanical behavior at small and large strains [11], in the thermo‐mechanical behavior [3] and in thermal expansion [4].…”
Section: Introductionmentioning
confidence: 99%
“…The material response at small deformation was investigated by means of uniaxial tensile tests, whereas compression tests were employed to investigate the large (i.e., yield and postyield) deformation levels. Particular attention was reserved to the investigation of the large deformation response, in the attempt to understand the correlation between the molecular architecture of polymer glassy networks and their mechanical behavior, on the framework of the approach developed in other works [6–10, 23, 24]. Most of these papers focused their attention on epoxy‐based systems [6, 7, 9, 10, 23], in which different crosslink densities and structures were varied by changing the nature of the hardener; also other crosslinked materials were studied, such as crosslinked polythiourethane systems [8] and amorphous polystyrene–polyphenylene oxide blends, crosslinked during polymerization [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation